Determination of Total Mercury in Fish from Amur and Ussuri River of China by Microwave Digestion-ICP/MS Method - Qin, Dongli; Chen, Zhongxiang; Wang, Haitao; Zhao, Jiwei; Mou, Zhenbo (Asian Journal of Chemistry, 2013)
Total mercury concentration in fishes from Fuyuan reach of the Amur and Ussuri River were determined by inductively coupled plasma-mass spectrometry. Sample analysis consisted of digestion of 0.5 g of muscle with nitric acid and hydrogen peroxide solution using microwave digestion, followed quantification of mercury by ICP-MS, Bi was used as an internal standard (ISTD). The mean recovery ranged from 95.2-105.8 % and the relative standard deviation (RSD) ranged from 2.84 to 7.22 % and the lower limit of detection was 0.001 mg/kg. The present study showed that total mercury in specimens of Parasiburusasvtus and Pelteobagrus fulvidraco were generally higher than in Cyprinus carpio Linnaeu and Carassius auratu gibeliv, but total mercury concentrations in all the samples below 0.3 mg/kg, limit recommended by China regulation.